Dosimetric impact of different multileaf collimators on prostate intensity modulated treatment planning - Orlandini, Lucia Clara (Rep Pract Oncol Radiother, 2015)
AIM: The main purpose of this study is to perform a dosimetric comparison on target volumes and organs at risks (OARs) between prostate intensity modulated treatment plans (IMRT) optimized with different multileaf collimators (MLCs). BACKGROUND: The use of MLCs with a small leaf width in the IMRT optimization may improve conformity around the tumor target whilst reducing the dose to normal tissues. MATERIALS AND METHODS: Two linacs mounting MLCs with 5 and 10 mm leaf-width, respectively, implemented in Pinnacle(3) treatment planning system were used for this work. Nineteen patients with prostate carcinoma undergoing a radiotherapy treatment were enrolled. Treatment planning with different setup arrangements (7 and 5 beams) were performed for each patient and each machine. Dose volume histograms (DVHs) cut-off points were used in the treatment planning comparison. RESULTS: Comparable planning target volume (PTV) coverage was obtained with 7- and 5-beam configuration (both with 5 and 10 mm MLC leaf-width). The comparison of bladder and rectum DVH cut-off points for the 5-beam arrangement shows that 52.6% of the plans optimized with a larger leaf-width did not satisfy at least one of the OARs’ constraints. This percentage is reduced to 10.5% for the smaller leaf-width. If a 7-beam arrangement is used the value of 52.6% decreases to 21.1% while the value of 10.5% remains unchanged. CONCLUSION: MLCs collimators with different widths and number of leaves lead to a comparable prostate treatment planning if a proper adjustment is made of the number of gantry angles.